Resolving some nomenclatural issues on Isoeto-Nanojuncetea and four new communities of the Iberian Peninsula - Silva, Vasco (2021)
We describe four new vegetation units and propose 17 new typifications and 24 altered names of syntaxa belonging to Isoeto-Nanojuncetea. Information is also provided on the publication dates of the alliances Isoetion and Preslion